Member for seal material and seal material
By bonding resin layers to foam members with exposed cell surfaces, the sealing material efficiently addresses material waste in manufacturing, ensuring strong bonding and effective water-stopping performance.
Patent Information
- Application Number
- JP2023113318
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-10
- Publication Date
- 2025-01-23
AI Technical Summary
The conventional method of manufacturing sealing members for battery cases results in significant material waste due to the punching process, which is more pronounced as the size of the object to be water-stopped increases.
A sealing material comprising a foam with exposed cell surfaces and a resin layer, where the resin layers of multiple members are bonded together, reducing material loss by optimizing the punching process to fit the shape of the object.
This approach significantly reduces material waste by allowing the sealing material to be formed without wasting central portions, enhancing bonding strength, and maintaining effective water-stopping properties.
Smart Images

Figure 2025010975000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a member for a sealing material and a sealing material. [Background technology]
[0002] Conventionally, an on-board battery used in an electric vehicle is housed in a battery case, and the battery case has a water-tight property enhanced by a sealing member from the viewpoint of preventing the intrusion of water from the external environment. In Patent Document 1, foamed rubber is used as a sealing member for a battery case. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent Publication No. 2011-194982 Summary of the Invention [Problem to be solved by the invention]
[0004] The general method for manufacturing sealing members is to punch out flat raw materials. Since sealing members are formed into rings to fit waterproof objects such as battery cases, punching out the material wastes the central part of the raw material. This type of material loss becomes more noticeable as the size of the waterproof object increases. The present invention has been made in consideration of the above-mentioned problems, and has an object to provide a technology relating to a sealing material that can reduce material waste. [Means for solving the problem]
[0005] One aspect of the present invention is a member for a sealing material, which comprises a foam having at least a first cell surface where cells are exposed and a second cell surface where cells are exposed, and a resin layer, the resin layer including at least a first resin layer formed on the first cell surface and a second resin layer formed on the second cell surface. In the member for a sealing material of the above aspect, the resin layer may contain a silicone-based resin. The foam may be a silicone foam. Another aspect of the present invention is a sealing material, in which the resin layers of the above-mentioned plurality of sealing material members are bonded together. The sealing material of the above embodiment may be used for a battery case. Effect of the Invention
[0006] According to the present invention, a technique for a sealing material that can reduce material loss can be provided. [Brief description of the drawings]
[0007] [Figure 1] FIG. 1 is a schematic plan view of a sealing material and a member according to an embodiment. [Diagram 2] Fig. 2(a) is a schematic plan view of the member, and Fig. 2(b) and Fig. 2(c) are perspective views of the foam 20 from different viewpoints. [Diagram 3] FIG. 3 is a schematic diagram of a sealing material according to an embodiment. [Figure 4] 4(a) to 4(c) are diagrams showing a manufacturing process (a process of joining members together) of a sealing material according to an embodiment. [Diagram 5] FIG. 5 is a schematic process diagram of the sealant used in the waterproofing evaluation. [Figure 6] FIG. 6 is a diagram showing the arrangement of a plurality of members when they are punched. [Figure 7] FIG. 7 is a cross-sectional view showing an outline of an evaluation device used in the waterproofing evaluation. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Hereinafter, embodiments of the present invention will be described in detail. In this specification, the expression "a to b" in the explanation of a numerical range means that the range is from a to b, unless otherwise specified.
[0009] (Sealing material) FIG. 1 is a schematic plan view of a sealing material 100 and a member 10 according to an embodiment. The shape of the sealant 100 (the outline of which is shown by a dotted line in FIG. 1) is appropriately changed according to the shape of the object to be sealed (sealed) for which water-stopping properties are required. In FIG. 1, the sealant 100 is a polygonal annular member, but it may also be a (substantially) rectangular, (substantially) circular, or (substantially) elliptical annular member. The member 10 forms a part of a plurality of regions obtained by dividing the sealing material 100. As will be described later, the sealing material 100 is formed by joining a plurality of members 10 together.
[0010] Fig. 2(a) is a schematic plan view of a member 10. As shown in Fig. 2(a), the member 10 includes a foam 20 and a resin layer 30. Fig. 2(b) and Fig. 2(c) are perspective views of the foam 20 from different viewpoints.
[0011] <Foam> As shown in Fig. 2(b) and Fig. 2(c), the foam 20 has at least a first cell surface 22 where the cells are exposed, and a second cell surface 24 where the cells are exposed. In this embodiment, the foam 20 has a rectangular parallelepiped shape with bent portions (a rectangular shape with bent portions when viewed in a plan view). In the axial direction of the foam 20 (the longitudinal direction when viewed in a plan view), a pair of opposing end faces respectively form the first cell surface 22 and the second cell surface 24. In this specification, the term "cell surface" refers to a cross section where a large number of cells are exposed.
[0012] Examples of materials for forming the foam 20 include silicone resins, fluorine resins, polyurethane resins, polypropylene resins, polyester resins, polyethylene resins, polyvinyl chloride resins, acrylic resins, phenol resins, epoxy resins, vinyl ester resins, polyamide resins, polyurea resins, vinyl ether resins, and rubber resins. Of these materials, it is preferable to use silicone resins. In other words, it is preferable that the foam 20 is a silicone foam.
[0013] The silicone resin is not particularly limited as long as it contains a silane compound as a raw material monomer, and dimethyl silicone, methylphenyl silicone, and various modified silicones (for example, amino-modified silicone, epoxy-modified silicone, polyether-modified silicone emulsion, alkyl-modified silicone emulsion, fluorine-modified silicone, etc.) can be used. The silicone resin may be a copolymer such as a silicone-acrylic copolymer.
[0014] It is more preferable that the member 10 is a closed-cell foam. When the member 10 is a closed-cell foam, when a resin composition (which becomes a resin layer 30 after curing) described later is applied (for example, coated or attached) to the first cell surface 22 or the second cell surface 24 of the member 10, the resin composition can be prevented from seeping into the member 10 through the cells. Therefore, the resin composition remains near the first cell surface 22 or the second cell surface 24 of the member 10, so that a high bonding strength between the members 10 can be achieved.
[0015] In addition to the materials mentioned above, the foam 20 may contain other components, for example additives such as colorants such as pigments, fillers, antioxidants, and ultraviolet protection agents.
[0016] A skin layer (a surface layer with almost no air bubbles) may be formed on the flat and bottom surfaces of the foam 20. When the foam 20 has a skin layer, the adhesion to the waterproof object (adherend) can be improved, and the waterproof property of the sealing material formed using a plurality of members 10 can be further improved.
[0017] The density of the foam 20 can be adjusted appropriately depending on the application of the sealing material 100. The density of the foam 20 is, for example, 0.020 g / cm 3 More than 0.030g / cm 3 More than 0.040g / cm 3 More than 0.050g / cm 3 More than 0.075g / cm 3 More than 0.100g / cm 3 More than 0.120g / cm3 or more, and 0.950 g / cm 3 Below 0.800g / cm 3 Below, 0.700g / cm 3 Below, 0.600g / cm 3 Below 0.550g / cm 3 Below 0.500g / cm 3 Below, 0.450g / cm 3 Below, 0.400g / cm 3 Below 0.350g / cm 3 Below, 0.300g / cm 3 By setting the density of foam 20 within this range, sealing material 100 can be used for a wider range of applications. Note that "density" refers to the apparent density measured in accordance with JIS K7222:2005 "Foamed plastics and rubber - Determination of apparent density."
[0018] In the foam 20, the average cell diameter in a cross section perpendicular to a plane (for example, a skin layer) is not particularly limited and is, for example, preferably 5 μm to 300 μm, more preferably 5 μm to 200 μm, and further preferably 5 μm to 100 μm.
[0019] The average cell diameter in a cross section perpendicular to the plane (e.g., the skin layer) of the foam 20 can be measured by the following method.
[0020] Using a scanning electron microscope (SEM, for example, VHXD-500, manufactured by Keyence Corporation), a cell photograph of a cross section perpendicular to the plane (for example, skin layer) of the foam 20 is taken. Then, using image processing software {for example, Image-ProPLUS (manufactured by Media Cybernetics, 6.3ver)}, each cell diameter is measured. More specifically, the SEM image is read, and the contrast is adjusted in order to recognize the cells by contrast. Next, the shape of the cell is read by image processing (recognizing the shape as it is, not a perfect circle). Next, "diameter (average)" is selected as the measurement item. Next, the diameter passing through the center of gravity of the object is measured at 2 degree intervals, and each cell diameter is calculated as the average value.
[0021] The porosity of the foam 20 is preferably 10% or more, 15% or more, or 20% or more, and is preferably 50% or less, 45% or less, or 40% or less.
[0022] The void ratio of the foam 20 is calculated as a percentage by dividing the apparent density of the foam 20 after foaming by the density of the unfoamed raw resin, and subtracting this divisor from 1. The apparent density is measured in accordance with JIS K7222:2005 "Polymers and rubber - Determination of apparent density".
[0023] <Resin layer> The resin layer 30 includes at least a first resin layer 32 formed on the first cell surface 22 of the foam 20 and a second resin layer 34 formed on the second cell surface 24 of the foam. The resin layer 30 is preferably formed from one or more resin compositions selected from the group consisting of silicone-based resins, polyurethane-based resins, acrylic-based resins, vinyl ether-based resins, epoxy-based resins, and rubber-based resins. Among these, from the viewpoint of the foam 20, it is preferable that the resin layer 30 is formed from a silicone-based resin.
[0024] The silicone-based resin is not particularly limited, and can be appropriately selected from known silicone-based resins, such as silicone rubber or silicone resin containing organopolysiloxane as the main component, which is cured by adding a crosslinking agent such as a siloxane-based crosslinking agent or a peroxide-based crosslinking agent.
[0025] The polyurethane resin is not particularly limited, and examples thereof include adhesives that utilize two-component curing urethane resins that contain various polyol compounds such as polyether polyols, polyester polyols, acrylic polyols, and polycarbonate diols, and curing agents such as the various isocyanate compounds described above.
[0026] The acrylic resin is not particularly limited, and examples thereof include adhesives containing a resin whose main component is (meth)acrylic acid or a derivative thereof (such as methyl methacrylate).
[0027] The resin layer 10 may be formed of one kind alone or a mixture of two or more kinds of these resins.
[0028] The resin layer 30 may contain other components in addition to the above-mentioned resins. For example, known additives such as oil components (plasticizers), tackifier resins, antioxidants, waxes, heat stabilizers, and fillers may be blended as other components. These additives may be used alone or in combination of two or more.
[0029] The material of the resin layer 30 preferably contains the same type of resin as the material of the foam 20. For example, the material of the resin layer 30 and the material of the foam 20 preferably both contain a silicone-based resin, a polyurethane-based resin, an acrylic-based resin, a vinyl ether-based resin, an epoxy-based resin, or a rubber-based resin. In this way, by forming the material of the resin layer 30 and the material of the foam 20 from the same type of resin, the affinity between the foam 20 and the resin layer 30 can be increased, and the bonding strength between the foam 20 and the resin layer 30 can be increased.
[0030] The thickness of the first resin layer 32 and the second resin layer 34 is preferably 300 μm or less, 200 μm or less, 150 μm or less, or 130 μm or less, respectively.
[0031] Moreover, the thickness of the first resin layer 32 and the second resin layer 34 is preferably 50 μm or more, 60 μm or more, 70 μm or more, 80 μm or more, or 90 μm or more, respectively.
[0032] By setting the thicknesses of the first resin layer 32 and the second resin layer 34 within the above ranges, a high level of bonding strength between the members 10 can be achieved.
[0033] (Sealing material) Fig. 3 is a schematic diagram of a sealing material 100 according to an embodiment. The sealing material 100 is a composite body in which a plurality of members 10 (four members 10, namely, members 10a, 10b, 10c, and 10d, are bonded together in the example of Fig. 3). In a pair of adjacent members 10, the first resin layer 32 of one member 10 and the second resin layer 34 of the other member 10 are bonded together. Specifically, the first resin layer 32a of the member 10a is bonded to the second resin layer 34a of the member 10b. The first resin layer 32b of the member 10b is bonded to the second resin layer 34c of the member 10c. The first resin layer 32c of the member 10c is bonded to the second resin layer 34d of the member 10d. Also, the first resin layer 32d of the member 10d is bonded to the second resin layer 34a of the member 10a.
[0034] In the seal material 100, in a pair of joined members 10, an interface exists between the first resin layer 32 of one member 10 and the second resin layer 34 of the other member 10.
[0035] In a pair of adjacent members 10, the surfaces where the first resin layer 32 of one member 10 and the second resin layer 34 of the other member 10 come into contact with each other are modified by plasma treatment, thereby increasing the bonding strength between the pair of adjacent members 10.
[0036] The sealing material 100 of this embodiment is formed by joining a plurality of members 10, so that when the plurality of members 10 are produced by punching, the punching regions can be arranged efficiently according to the shapes of the individual members 10 (for example, when the number of members 10 is two, see FIG. 6). Therefore, compared to when the entire sealing material is formed by punching, it is possible to significantly reduce material loss. The effect of reducing material loss becomes even more remarkable as the size of the sealing material becomes larger.
[0037] One embodiment of the sealing material is described below. (Item 1) A composite in which air bubble exposed surfaces of a plurality of foam bodies are bonded to each other, A sealing material, wherein the joints of the plurality of foam bodies are joined with a resin layer containing a silicone-based resin. (Item 2) 2. The sealant according to item 1, wherein the foam is a silicone foam. (Item 3) 3. The sealing material according to claim 1 or 2, wherein the foam is a closed-cell foam. (Item 4) the resin layer includes a first resin layer and a second resin layer, 2. The sealing material according to item 1, wherein the surfaces of the first resin layer and the second resin layer that come into contact with each other have been modified by plasma treatment.
[0038] <Method of manufacturing the sealing material> One embodiment of a method for producing the sealing material 100 will be described. First, as shown in Fig. 4(a), a pair of foam bodies 20 are prepared, and a first resin layer 32 is formed on the first cell surface 22 of one foam body 20 to obtain a member 10i. A second resin layer 34 is formed on the second cell surface 24 of the other foam body 20 to obtain a member 10j. The first resin layer 32 and the second resin layer 34 can be formed by applying and curing a resin composition. When forming the first resin layer 32 and the second resin layer 34, a film or flat plate having a smooth surface and releasability, such as a PET film or an acrylic plate, may be laminated on the resin composition after the resin composition is applied, and the film or flat plate may be peeled off after the resin composition is cured. This can increase the smoothness of the surfaces of the first resin layer 32 and the second resin layer 34, and thus increase the adhesion and bonding between the first resin layer 32 and the second resin layer 34.
[0039] Next, as shown in FIG. 4(b), the first resin layer 32 and the second resin layer 34 are each irradiated with plasma. Plasma irradiation is a process in which a gas is used to bombard the plasma onto at least a part of the surface of an object. Examples of plasma irradiation include low-pressure plasma irradiation and atmospheric pressure plasma irradiation. In this embodiment, atmospheric pressure plasma irradiation is preferred from the viewpoint of cost and workability. Since atmospheric pressure plasma irradiation does not require a device for creating a low-pressure environment, it is possible to reduce costs and has excellent workability. In addition, since high-speed processing can be performed any number of times on any part to be subjected to plasma irradiation, localized and high-density plasma irradiation can be performed. The gas used for plasma irradiation is not particularly limited, and examples include nitrogen (N2), oxygen (O2), carbon dioxide (CO2), argon (Ar), helium (He), etc. Alternatively, a mixed gas of two or more of these gases may be used. The plasma output, gas flow rate, vacuum level, processing time, etc. can be adjusted. The processing conditions can be adjusted based on the wettability and spreading degree of the resin layer.
[0040] 4(c), the first resin layer 32 of the member 10i and the second resin layer 34 of the member 10j are pressure-bonded to join the members 10i and 10j. The pressure-bonding time is, for example, 1 to 10 seconds.
[0041] By applying the joining process for joining components shown in Figures 4(a) to 4(c) to adjacent components for all components constituting the sealing material, it is possible to produce a sealing material 100 as illustrated in Figure 3.
[0042] According to the above-described method for manufacturing the sealing material, since there is no need to carry out a curing step or a standing step after joining the members 10 together, the work can be simplified and made more efficient, and ultimately the manufacturing cost of the sealing material can be reduced.
[0043] Furthermore, in a pair of adjacent members 10, the first resin layer 32 of one member 10 and the second resin layer 34 of member 10j are each subjected to plasma treatment, and then the pair of members 10 are pressure-bonded to each other, thereby sufficiently increasing the bonding strength.
[0044] One embodiment of a method for bonding foam pieces together is described below. (Item 5) forming a first resin layer on a cell surface of one of the pair of foam bodies and a second resin layer on a cell surface of the other of the pair of foam bodies; a step of exposing the first resin layer and the second resin layer to plasma; a step of pressure-bonding the plasma-irradiated first resin layer and the second resin layer; A method for bonding foam bodies, comprising:
[0045] One embodiment of a method for producing the composite is described below. (Item 6) A method for producing a composite formed of a plurality of members including a first member and a second member, comprising the steps of: a first resin layer forming step of forming a first resin layer, the first resin layer including a silicone-based resin on an exposed surface of the first member, the first member being a foam having an exposed surface on which air bubbles are exposed, the first resin layer having a flat surface opposite to the exposed surface; a second resin layer forming step of forming a second resin layer on the exposed surface of the second member, which is a foam having an exposed surface on which air bubbles are exposed, the second resin layer including a silicone-based resin and having a flat surface opposite to the exposed surface; a first treatment step of irradiating a flat surface of the first resin layer with plasma to form a first treated surface; a second treatment step of irradiating the flat surface of the second resin layer with plasma to form a second treatment surface; a step of pressing the first treated surface and the second treated surface together to bond the first member and the second member; A method for producing a composite, comprising:
[0046] One embodiment of a method for manufacturing the annular member is described below. (Item 7) A method for manufacturing an annular member, in which a plurality of foam bodies are formed adjacent to each other in an annular shape, comprising the steps of: For each foam, forming a resin layer containing a silicone-based resin on the two bubble exposed surfaces and having a flat surface opposite to the exposed surfaces; Plasma is irradiated onto each flat surface of the resin layer at the bubble-exposed surface; In all pairs of adjacent foam bodies, the flat surface of one foam body that has been subjected to the plasma irradiation is pressed against the flat surface of the other foam body that has been subjected to the plasma irradiation to bond them together. A method for manufacturing an annular member. (Item 8) 8. The method for producing an annular member according to item 7, wherein the annular member is a sealing material.
[0047] <Applications of sealing materials> The seal material 100 can be widely used for waterproof objects that require waterproofing, for example, as a seal material for battery cases, a seal material (packing) installed in pipe joints, and the like.
[0048] Although the embodiments of the present invention have been described above, these are merely examples of the present invention, and various configurations other than those described above can also be adopted. EXAMPLES
[0049] The present invention will be described below with reference to examples, but the present invention is not limited to these.
[0050] (Bonding strength evaluation) <Production of test specimens for evaluating bonding strength> <Test item 1> Two foam pieces (silicone foam, manufactured by Rogers Inoac Corp., NanNexTL-7404) measuring 65 mm × 30 mm × 5 mm were prepared. Silicone-based resin 1 shown in Table 1 was applied to the cellular surface of one foam and the cellular surface of the other foam to a thickness of 130 μm. Table 1 shows the properties of each silicone-based resin (density, viscosity, 25% CLD, and tensile strength when cured). The viscosity is a value guaranteed by the manufacturer. For the 25% CLD, a sheet with a thickness of 1 mm was formed using each silicone resin, and a circular test piece with a diameter of 50 mm was punched out from the sheet, and measurement was performed at a speed of 1 mm / min in accordance with JIS K6254. The density was calculated by measuring the diameter, height, and weight of the test specimen for 25% CLD. For the tensile strength, each silicone resin was used to mold a sheet having a thickness of 1 mm, and a dumbbell-shaped No. 3 test piece was punched out from the sheet, and the test was performed at a speed of 200 mm / min in accordance with JIS K6251.
[0051] [Table 1]
[0052] The details of the materials shown in Table 1 are as follows: Silicone resin 1: SE9187L, manufactured by Dow Toray Co., Ltd. Silicone resin 2: SE9120, manufactured by Dow Toray Co., Ltd. Silicone resin 3: SE9189L, manufactured by Dow Toray Co., Ltd.
[0053] Next, a smooth acrylic plate was attached to each surface of the applied silicone-based resin 1, and each surface of the silicone-based resin 1 was smoothed and left to stand until the silicone-based resin 1 was cured. The acrylic plate was peeled off, and each smoothed surface of the silicone-based resin 1 was irradiated with plasma using a plasma irradiation device "Atmospheric Pressure Multi-Gas Plasma Jet Source" {SPR-DFMJ-01 (50 Hz)} (manufactured by Sunline Co., Ltd.) under the following conditions. Gas for plasma irradiation: Oxygen (O2) Irradiation distance: 2mm Irradiation time: 5 seconds Gas flow rate: 8L / min The two foams were pressed together for three seconds so that the plasma-irradiated silicone resins 1 were in contact with each other. Through the above steps, a test sample 1 for evaluating the bonding strength was produced.
[0054] <Test sample 2> Test sample 2 was produced in the same manner as test sample 1, except that silicone-based resin 2 shown in Table 1 was used instead of silicone-based resin 1.
[0055] <Test item 3> Test sample 3 was produced in the same manner as test sample 1, except that silicone resin 3 shown in Table 1 was used instead of silicone resin 1.
[0056] <Measurement> The tensile strength of test pieces 1 to 3 was measured in accordance with JIS K6251:2010 "Vulcanized rubber and thermoplastic rubber - Determination of tensile properties". Specifically, for each test piece, a dumbbell-shaped No. 3 punched test piece was prepared so that the joint was located in the center, and a tensile test was performed using an Instron material testing machine (Shimadzu Corporation, Autograph) at a crosshead speed of 200 mm / min to measure the joint strength. The joint strength was evaluated as follows. The results obtained for the joint strength are shown in Table 2.
[0057] [Table 2]
[0058] (Water-stopping evaluation) <Production of sealing material (test item for evaluating watertightness)> <Example 1> As shown in FIG. 5, a foam (silicone foam, Inoac Corporation, NanNex TL-7404, density: 0.400 g / cm) was used as a semi-doughnut-shaped member with an outer diameter of 60 mm, an inner diameter of 40 mm, and a thickness of 5 mm. 3 ) were prepared. The foam components can be obtained by punching out flat foam in an arrangement that minimizes the gaps (waste areas) between the foam components, as shown in Figure 6. This allows the foam raw material to be used effectively while minimizing waste. Silicone-based resin 1 shown in Table 1 was applied to the cellular surface of each foam to a thickness of 130 μm. A smooth acrylic plate was attached to each surface of the applied silicone-based resin 1, and each surface of the silicone-based resin 1 was smoothed and left to stand until the silicone-based resin 1 was cured. The acrylic plate was peeled off, and each smoothed surface of the silicone-based resin 1 was subjected to plasma irradiation using a plasma irradiation device "Atmospheric Pressure Multi-Gas Plasma Jet Source" {SPR-DFMJ-01 (50 Hz)} (manufactured by Sunline Corporation) under the following conditions. Gas for plasma irradiation: Oxygen (O2) Irradiation distance: 2mm Irradiation time: 5 seconds Gas flow rate: 8L / min The two foams were pressed together for three seconds so that the silicone-based resins 1 after plasma irradiation were in contact with each other. Through the above steps, a sealing material of Example 1 having a doughnut (annular) shape as shown in FIG.
[0059] <Example 2> A sealing material of Example 2 was produced in the same manner as in Example 1, except that silicone resin 2 shown in Table 1 was used instead of silicone resin 1.
[0060] <Example 3> A sealing material of Example 3 was produced in the same manner as in Example 1, except that silicone resin 3 shown in Table 1 was used instead of silicone resin 1.
[0061] <Reference example> As a reference example, a foam (silicone foam, NanNex TL-7404, manufactured by Inoac Corporation, density: 0.400 g / cm) with an outer diameter of 60 mm, an inner diameter of 40 mm, and a thickness of 5 mm was punched out. 3 ) was prepared.
[0062] <Measurement> 7 is a cross-sectional view showing an overview of the evaluation device 200 used in the water-stopping evaluation. The sealing material 100 of each of the examples and the reference example was placed on a metal plate 210a having a thickness of 10 mm. A spacer 220 having a thickness of 2.5 mm was placed around the sealing material 100, and an acrylic plate 210b having a thickness of 10 mm was used to fix the sealing material 100 in a state in which the sealing material 100 was compressed to a compression rate of 50%. Measurement was started after the sealing material 100 was installed. Specifically, the inner circular portion of the annular sealing material 100 was filled with about 2.0 g of distilled water via the inlet pipe 230 communicating with the inner circular portion of the sealing material 100, and then air was supplied at a pressure of 0.5 kgf / cm. 2 This state was maintained for 5 minutes, and if there was no water leakage, air was further supplied to maintain a static pressure of 0.1 kgf / cm 2 Add 0.6kgf / cm 2 The test piece was then placed in a container and held for one minute. This procedure was repeated until water leakage occurred, and the pressure at which water leakage occurred was measured. The results of water leakage (water-stopping pressure) are shown in Table 3.
[0063] [Table 3]
[0064] The sealing materials of Examples 1 to 3 have a water-stopping pressure of 1.5 kgf / cm 2 As a result, it was confirmed that there were no practical problems. [Explanation of symbols]
[0065] 10 member, 20 foam, 22 first foam surface, 24 second foam surface, 30 resin layer, 32 first resin layer, 34 second resin layer, 200 evaluator, 210a metal plate, 210b acrylic plate, 220 spacer, 230 introduction tube
Claims
1. The foam has at least a first cell surface where the cells are exposed and a second cell surface where the cells are exposed, and a resin layer; The resin layer includes at least a first resin layer formed on the first bubble surface and a second resin layer formed on the second bubble surface.
2. The member for a sealing material according to claim 1 , wherein the resin layer contains a silicone-based resin.
3. 3. The member for a sealing material according to claim 1 or 2, wherein the foam is a silicone foam.
4. A sealing material, comprising a plurality of the resin layers of the members for a sealing material according to claim 1 or 2 bonded together.
5. The sealing material according to claim 4, which is for a battery case.
Citation Information
Patent Citations
Battery case for vehicle
JP2011194982A